The need for System Analysis and Automation In an aviation company - Balti, Ala; Lakhoua, Najeh Mohamed (Journal of Innovation and Applied Technology, 2025)
Through to the purchasing, customers can increase the availability of their assets and reduce their maintenance costs in the aviation industry and there is always an ongoing process of cost reduction, which must be done without interfering with the safety and airworthiness.In this study, we started with presentation of the environment and the general framework from which we developed our specification, which allowed us to define the methodology of our work. We started by builders recover documents then retrieve the list of codes existing database-level information system (AMASIS). Then, we integrate technical database characteristics of each ingredient and we consider the annual consumption of each N-1 reference.The aim of this paper is to study and implement a comprehensive database to get reliable and complete listing of ingredients used by an aviation company. Finally, trying some tests at the automatic replenishment module.